Evaluation of mechanical properties of asphalt mixtures with incorporation of aramid andpolypropylene synthetic fibers - Mardones Parra, Luis (2025)
Roads are exposed to external conditions such as rain, solar radiation and the increase of vehicular flow, among others; which generates distresses on asphalt pavements. It is necessary to research new technologies being able to improve the behavior of pavements against external conditions. Currently, the use of polymer modified asphalts is one of the most used alternatives, because they provide a greater durability to the pavement structure. However, literature review has shown that there are other competitive techniques to obtain good results, such as the use of synthetic fibers. Therefore, the main objective of this research is to evaluate the influence of the addition of aramid and polypropylene synthetic fibers in the mechanical properties of asphalt mixtures.For this purpose, a IV-A-12 asphalt mixture (mainly used in Chile) with a CA-24 asphalt binder (according to Chilean specifications) were manufactured, incorporating different percentages of synthetic fibers. The mechanical properties of the modified asphalt mixtures were compared with a reference hot asphalt mixture. Through the experimental phase, thermal cracking, moisture damage and rutting properties were evaluated. The results have shown that the use of aramid and polypropylene fibers in asphalt mixtures reduced the moisture damage and rutting, nevertheless the thermal cracking was improved.